Muhkam Mutasyabih - Kartono, Arsy Fathir; F, Fatmawati; Sunusi, Muh. Nur Taufiq (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In this paper, we will discuss further about Muhkam and Mutasyabah in the interpretation of the Al-Qur'an, as well as how Islamic religious experts understand and apply these concepts in the interpretation process. We will also discuss how Muhkam and Mutasyabah influence the interpretation of the Qur'an and how they help Islamic schoalars understand the meaning of the Qur'an better. In the process of interpretation, Islamic religious experts must understand the differences between Muhkam and Mutasyabah. They must understand that the Muhkam verses have a clear and undeniable meaning, while the Mutasyabah verses have meanings that can be interpreted differently. By understanding these differences, Islamic religious experts can carry out more accurate and deeper interpretations, thereby understanding the meaning of the Qur'an better.